Clonality assessment and clonal ordering of individual neoplastic crypts shows polyclonality of colorectal adenomas. - Thirlwell, C; Will, O; Domingo, E; Graham, T; McDonald, SA; Oukrif, D; Jeffrey, R; Gorman, M; Rodriguez-Justo, M; Chin-Aleong, J; Clark, S; Novelli, MR; et al. (2010)
BACKGROUND and AIMS: According to the somatic mutation theory, monoclonal colorectal lesions arise from sequential mutations in the progeny of a single stem cell. However, studies in a sex chromosome mixoploid mosaic (XO/XY) patient indicated that colorectal adenomas were polyclonal. We assessed adenoma clonality on an individual crypt basis and completed a genetic dependency analysis in carcinomas-in-adenomas to assess mutation order and timing. METHODS: Polyp samples were analyzed from the XO/XY individual, patients with familial adenomatous polyposis and attenuated familial adenomatous polyposis, patients with small sporadic adenomas, and patients with sporadic carcinoma-in-adenomas. Clonality was analyzed using X/Y chromosome fluorescence in situ hybridization, analysis of 5q loss of heterozygosity in XO/XY tissue, and sequencing of adenomatous polyposis coli. Individual crypts and different phenotypic areas of carcinoma-in-adenoma lesions were analyzed for mutations in adenomatous polyposis coli, p53, and K-RAS; loss of heterozygosity at 5q, 17p, and 18q; and aneuploidy. Phylogenetic trees were constructed. RESULTS: All familial adenomatous polyposis-associated adenomas and some sporadic lesions had polyclonal genetic defects. Some independent clones appeared to be maintained in advanced adenomas. No clear obligate order of genetic events was established. Top-down growth of dysplastic tissue into neighboring crypts was a possible mechanism of clonal competition. CONCLUSIONS: Human colorectal microadenomas are polyclonal and may arise from a combination of host genetic features, mucosal exposures, and active crypt interactions. Analyses of tumor phylogenies show that most lesions undergo intermittent genetic homogenization, but heterotypic mutation patterns indicate that independent clonal evolution can occur throughout adenoma development. Based on observations of clonal ordering the requirement and timing of genetic events during neoplastic progression may be more variable than previously thought.